Equal Treatment in Employment as an Imperative of Human Resource Management in Polish Conditions - Beata BIEŃKOWSKA (Communications of International Proceedings, 2023)
The most important fchallenges aced by modern organizations in the context of people management include: managing organizational change, managing equality and diversity in the workplace, as well as maintaining employee loyalty and commitment. For the purposes of this study, one of these challenges, namely equal treatment in employment, has been identified as a key area. This aspect has been referred to as an imperative, since shaping a work environment based on the indisputable foundation of equal treatment for all employees is not only part of an organization's social responsibility and is not only due to the "business" benefits that such an approach brings, but is also part of the regulatory environment that enforces compliance with the rules shaped by that environment. This article, therefore, analyzes the legal regulations that shape the behavior of organizations operating in Polish conditions, concerning equal treatment in employment. In this article, the author has limited her discussion to verifying the thesis that formal regulations on equal treatment of employees in Poland make a compelling case for the claim that equality in employment is an imperative of human resource management. However, one should be aware that the implementation of solutions in accordance with the current regulations on equal treatment requires action on many levels, which are related to the processes of education, building understanding of equality and, at the same time, diversity in the workplace, and cultural and social changes that are systematically and inexorably taking place in society
Keywords: human resources management; diversity management; equality; inclusion